2020
DOI: 10.1182/blood.2019003986
|View full text |Cite
|
Sign up to set email alerts
|

Heme induces rapid endothelial barrier dysfunction via the MKK3/p38MAPK axis

Abstract: Several studies demonstrate that hemolysis and free heme in circulation causes endothelial barrier dysfunction and is associated with severe pathological conditions like acute respiratory distress syndrome, acute chest syndrome, and sepsis. Yet, the precise molecular mechanisms involved in the pathology of heme induced barrier disruption still remains to be elucidated. In this study, we investigated the role of free heme on the endothelial barrier integrity and the mechanisms of heme-mediated intracellular sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…This transient nature indicates that heme-induced barrier disruption is not caused by cell death, and raises the question on which of the signaling pathways involved in the regulation of EB integrity are modulated by heme. This observation is also consistent with a previous study that also showed a dose-dependent effect of heme on EB integrity, and that showed that heme used at a higher concentration (40µM) was associated with a more delayed disruption of EB integrity that was attributed to necroptotic cell death ( 25 ), but other pathways that are modulated by heme such as autophagy ( 47 49 ) and MKK3/p38MAPK ( 50 ) have also been recently associated with EB changes. It should be noted that our results also confirm that the EB of HUVECs behave similarly to pulmonary and microvascular endothelial cells in response to heme, supporting their use in our subsequent experiments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This transient nature indicates that heme-induced barrier disruption is not caused by cell death, and raises the question on which of the signaling pathways involved in the regulation of EB integrity are modulated by heme. This observation is also consistent with a previous study that also showed a dose-dependent effect of heme on EB integrity, and that showed that heme used at a higher concentration (40µM) was associated with a more delayed disruption of EB integrity that was attributed to necroptotic cell death ( 25 ), but other pathways that are modulated by heme such as autophagy ( 47 49 ) and MKK3/p38MAPK ( 50 ) have also been recently associated with EB changes. It should be noted that our results also confirm that the EB of HUVECs behave similarly to pulmonary and microvascular endothelial cells in response to heme, supporting their use in our subsequent experiments.…”
Section: Discussionsupporting
confidence: 92%
“…Together these results provide additional support for the concept that FEH can directly contribute to EB disruption in SCD. Of note, in a recent study, the mechanisms by which heme disrupts the EB were further elucidated and shown to involve endothelial cytoskeleton remodeling ( 50 ), paving the way for the study of these pathways in SCD. Finally, our results also demonstrate that the effects of heme on endothelial cells are not restricted to serum free conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lung specimens from ACS cases showed micro‐thrombotic occlusion, endothelial VWF deposition and arterial vessel re‐modelling with initial fibrotic processes, 54 fascinatingly all comparable to the histopathological findings in COVID‐19 55 . Importantly, heme‐mediated endothelial damage to alveolar cells is regulated by the p38 mitogen‐activated protein kinase (MAPK) pathway, which plays a crucial role in the biosynthesis of pro‐inflammatory cytokines and collagen production 56 . This key pathway is also upregulated in COVID‐19 as a result of decreased ACE2 tissue functionality consequent to viral binding, and may consequently promote endotheliitis, hypercoagulation and end‐stage fibrosis 57,58 …”
Section: Endothelial Cell‐related Disorders In Haematology: Post‐bonementioning
confidence: 62%
“…55 Importantly, heme-mediated endothelial damage to alveolar cells is regulated by the p38 mitogen-activated protein kinase (MAPK) pathway, which plays a crucial role in the biosynthesis of pro-inflammatory cytokines and collagen production. 56 This key pathway is also upregulated in COVID-19 as a result of decreased ACE2 tissue functionality consequent to viral binding, and may consequently promote endotheliitis, hypercoagulation and end-stage fibrosis. 57,58 In summary, post-BMT syndromes, vaso-occlusive organ dysfunction in SCD and COVID-19-associated endotheliitis share common pathological mechanisms including: i) dysregulation of the homeostasis of the endothelial milieu toward a pro-inflammatory and pro-thrombotic phenotype with thrombotic microangiopathy; ii) hyperproduction of inflammatory cytokines such as IL-6, IL-8 and TNF-a; [59][60][61][62] and iii) small vessel endotheliitis and endothelial barrier dysfunction, leading to oedema of the microvascular bed, protein and fibrin accumulation and subsequent fibrotic shift.…”
Section: Introductionmentioning
confidence: 99%
“…Heme, in free form, may also represent a hazardous pro-oxidant compound due to the presence of the central iron, a potential catalyst of harmful free radical generating processes [ 8 ]. Indeed, heme accumulation has been implicated as a pathological mediator in various inflammatory conditions such as sepsis [ 9 , 10 , 11 ], malaria [ 12 ], sickle cell disease [ 13 ], and atherosclerosis [ 14 ]; with its clearance by HO-1 implicated as a protective and anti-oxidative strategy in these and other diseases.…”
Section: Introductionmentioning
confidence: 99%